PEDIATRIC NURSING MODELLING APPROACH ON MOTHER'S KNOWLEDGE, PRACTICE ABILITY AND MATERNAL CONFIDENCE OF INFANT GROWTH AND DEVELOPMENT - Ariyanti Saleh (Universitas Airlangga, 2017)
Introduction: The first five years of age of a child is a critical time that will affect the child growth development process. Any untreated disorders may impair the process that subsequently influences quality of life of the child in the future. Therefore, it is imperative for a mother to optimize the growth development process. This study aimed to identify the effectiveness of health education with modelling approach on mother's knowledge, practice ability and maternal confidence of infant (0-6 months) growth and development. Method: A quasy eksperimental pre-post with control group design was used. The intervention given was health education with modelling approach related to lactation management and infant growth development stimulation. The research was conducted in Maros Regency wiht 81 samples (41 in the treatment group and 40 in the control group). Result: The wilcoxon test reveals that there was a signi fi cant difference between treatment and control group, accordingly, knowledge (p = 0.00, p = 0.01), practice ability (p = 0.00, p = 0,006) and maternal confidence (p = 0.03, p = 0.03). In addition, from mann whitney test, between the two group, the data obtained are: knowledge (p = 0,950), practice ability (p = 0.00) and maternal con fi dence (p = 0,061). Discussion: Health education with modelling approach conducting by nurse was effective in increasing knowledge, practice ability, maternal confidence breastfeeding and baby stimulation, which was in turn can optimize baby growth and development. That is why, community health nurses role should be increase by making community health nursing program as one of primary public health centre program.